Is diagnostic stewardship possible in solid organ transplantation?. Issue 5 (18th October 2022) - Husson, Jennifer; Bork, Jacqueline T.; Morgan, Daniel; Baddley, John W.
Abstract: Background: Diagnostic stewardship in solid organ transplant (SOT) recipients has the potential to help these vulnerable patients at risk for over‐testing and overtreatment. Methods: Herein, we review potential targets for diagnostic stewardship in SOT, such as Clostridioides difficile testing, urine cultures, molecular diagnostics, as well as novel areas of diagnostic stewardship. Results: Bundled interventions focused on appropriate C. difficile testing can result in a significant decrease in testing and clinical diagnosis of C. difficile infection without any harms related to delay in diagnosis. In otherwise stable renal transplant recipients after the first month of transplant, screening urine cultures have not been shown to improve outcomes. Novel targets that require additional study in the SOT population include noninvasive fungal diagnostics and cytomegalovirus testing strategies Conclusions: Diagnostic stewardship is an innovative approach to improve diagnosis and limit unnecessary antimicrobial use. While there has been little direct exploration of diagnostic stewardship in the SOT population, there is great potential for benefit given frequent testing with diagnostics that have imperfect sensitivity and specificity, and sometimes great cost. Diagnostic stewardship in the SOT population is indeed possible but will require a multidisciplinary effort to ensure that appropriates tests and benefits are realized.